Restoration seedbanks for mined land restoration - Turner, Shane; Cross, Adam; Just, Michael; Newton, V.; Pedrini, Simone; Tomlinson, Sean; Dixon, Kingsley (WILEY, 2022)
Restoration seedbanks have become a key infrastructure resource in efforts to restore damaged and degraded environments across the globe. Large-scale ecological restoration typically utilizes large volumes of valuable, usually wild-collected seeds, but insufficient knowledge of seed biology (including storage requirements in some cases) and ecology for many species continues to hamper the utility of restoration seedbanks to meet this rising demand. Poor germination and establishment when seeds are deployed from seedbanks can stem from factors such as premature seed collection, low seed quality, poor processing, handling and storage, variable seed quality from year to year, and, critically, insufficient understanding of seed dormancy, seed germination traits, and the ecological requirements for germination stimulation. While these factors may impact the success of seed-based ecological restoration both synergistically and idiosyncratically, they can be universally addressed by adopting best practice principles in seedbank management and operation and through an improved understanding of the seed biology and ecology of stored species. Drawing upon an industry case study in seedbanking for post-mining ecological restoration, we outline how optimizing seed storage conditions and a focus on seed biology and ecology in the operation of a restoration seedbank can deliver broad and immediate benefit and cost-efficiency to native seed use. Such improvements are crucial in developing more effective approaches for returning biodiverse plant communities to highly modified landscapes and are foundational for meeting the aspirations for ecological restoration at global scales in the coming decade.